2019
DOI: 10.1177/0046958018825061
|View full text |Cite
|
Sign up to set email alerts
|

High Medicaid Nursing Homes: Organizational and Market Factors Associated With Financial Performance

Abstract: High Medicaid nursing homes (85% and higher of Medicaid residents) operate in resource-constrained environments. High Medicaid nursing homes (on average) have lower quality and poorer financial performance. However, there is significant variation in performance among high Medicaid nursing homes. The purpose of this study is to examine the organizational and market factors that may be associated with better financial performance among high Medicaid nursing homes. Data sources included Long-Term Care Focus (LTCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Moreover, in recent decades, there has been an increase in the growth of chain affiliation in the NH industry [ 11 ]. The affiliation of for-profit NHs with chains has been addressed in the literature that analyses the performance of NHs, especially in relation to financial performance [ 11 , 14 , 15 , 16 ] and, to a lesser extent, in relation to quality [ 12 , 17 , 18 ]. Belonging to a chain allows the standardisation of certain care processes, which can contribute to improving [ 19 ] or worsening the quality [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in recent decades, there has been an increase in the growth of chain affiliation in the NH industry [ 11 ]. The affiliation of for-profit NHs with chains has been addressed in the literature that analyses the performance of NHs, especially in relation to financial performance [ 11 , 14 , 15 , 16 ] and, to a lesser extent, in relation to quality [ 12 , 17 , 18 ]. Belonging to a chain allows the standardisation of certain care processes, which can contribute to improving [ 19 ] or worsening the quality [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, on a national basis, the STM benchmark is not economically feasible for most NHs. The average profit margin of NHs is below 1% ( Weech-Maldonado et al, 2019 ), and increased operating expenditures to reach the STM benchmark would cause a significant number of NHs to become unprofitable. Without being offset by additional revenue, implementing the STM benchmark would cause nearly three quarters of the NH industry to lose money providing services to residents and could result in the majority of NHs declaring bankruptcy or closing.…”
Section: Discussionmentioning
confidence: 99%
“…These measures were carefully selected based upon a comprehensive literature review and have been shown in prior research to be associated with nancial performance of nursing homes and other health care organizations. [10,[29][30][31][32][33][34] Total de ciencies was lagged by one year in the analytical models to address the endogeneity arising from improved quality of care derived from HIT adoption having a positive in uence on nancial performance. [11,29] See Table 1 for the data source of these measures, their de nition/operationalization in the study (Table 1).…”
Section: Control Variablesmentioning
confidence: 99%